StACS3-mediated drought stress adaptation in potato involves interactions with StPP2C2 and St14-3-3 proteins - Hamera, Sadia; Chaudhary, Safee Ullah; Lemcke, Heiko; Sklorz, Martin; Schilling, Florian; Schumacher, Christina; Huckauf, Jana; Zimmerman, Ralf; Horn, Renate; Uptmoor, Ralf (Frontiers in Plant Science, 2025)
Ethylene plays a critical role in plant development and stress adaptation, with its biosynthesis tightly regulated by the stability of 1-aminocyclopropane-1-carboxylic acid synthase (ACS) proteins. Here, we investigate the potato isozyme StACS3 and its role in modulating ethylene biosynthesis and drought tolerance. StACS3 transcript and protein levels are specifically upregulated under drought stress. In contrast, silencing StACS3 significantly reduces stress-induced ethylene accumulation and enhances drought resilience, including decreased cell death and increased antioxidant activity. Heterologous expression of StACS3 in Arabidopsis thaliana induces severe developmental phenotypes, such as compact growth, reduced root development, sterility, and accelerated leaf senescence, demonstrating its influence on ethylene-associated processes. Mechanistically, StACS3 is regulated post-translationally through interactions with StPP2C2, a type 2C protein phosphatase that promotes proteasome-mediated degradation, and St14-3-3, a phospho-binding protein that stabilizes StACS3. Mutation and co-expression analysis support the formation of StACS3-StPP2C2 complexes, and silencing StPP2C2 increases StACS3 accumulation and alters its subcellular localization, demonstrating an antagonistic interplay between degradation and stabilization pathways. Collectively, these findings reveal a dynamic post-translational regulatory module that fine-tunes ethylene biosynthesis during drought stress. This study establishes StACS3 as a central node in ethylene-mediated drought response pathways in potatoes, providing mechanistic insights into the balance of protein degradation and stabilization that underlies stress adaptation.